Green synthesis of P − ZrO2CeO2ZnO nanoparticles using leaf extracts of Flacourtia indica and their application for the photocatalytic degradation of a model toxic dye, Congo red. Issue 8 (August 2022) - Hokonya, Nichodimus; Mahamadi, Courtie; Mukaratirwa-Muchanyereyi, Netai; Gutu, Timothy; Zvinowanda, Caliphs
Abstract: In the present work P − Z r O 2 C e O 2 Z n O nanoparticles were synthesised for the first time using phytochemical extracts from Flacourtia indica leaves and applied in the photocatalytic degradation of Congo Red in the presence of Light Emitting Diode warm white light. The photocatalytic degradation was optimized with respect to P − Z r O 2 C e O 2 Z n O nanoparticle dosage, initial Congo Red concentration, and degradation time. The optimum conditions for P − Z r O 2 C e O 2 Z n O nanoparticle synthesis was pH 9, leaves extracts of F. indica dosage 4 g 100 mL −1, Zirconia, Cerium and Zinc metal ion concentration 0.05 mg/L and metal ion to plant volume ratio of 1:4. The leaves extract dosage, pH and metal concentration had the most significant effects on the synthesis of the nanoparticles. The nanoparticles followed type III physisorption adsorption isotherms with surface area of 0.4593 m 3 g −1, pore size of 6.80 nm, pore volume 0.000734 cm g − 1 3 and average nanoparticle size 0.255 nm. A degradation efficiency of 86% was achieved and the optimum degradation conditions were 0.05 g/L of P − Z r O 2 C e O 2 Z n O nanoparticle dosage, 10 mg/L initial Congo red concentration, and 250 minutes irradiation time. Data from kinetic studies showed that the degradation followed pseudo first order kinetics at low concentration, with a rate constant of 0.069 min −1 . The superoxide, h + holes and light were the main determinants of the reaction mechanisms for the degradation of Congo Red. The investigation outcomes demonstrated that P − Z r O 2 C e O 2 Z n O nanoparticles offer a high potential for photocatalytic degradation of Congo Red. Graphical abstract: Highlights: The most significant factors on P − Z r O 2 C e O 2 Z n O nanoparticles synthesis were plant leaves dosage, pH and initial metal concentration. The nanoparticles exhibited high catalytic activity towards photocatalytic degradation of Congo red. Superoxide, h + holes and light were the main determinants of the photocatalytic degradation mechanisms. Abstract : Flacourtia indica; P − Z r O 2 C e O 2 Z n O nanoparticles; Reaction mechanisms; Congo red; Photocatalysis